2016
DOI: 10.1016/j.lfs.2016.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib promotes degranulation of CD8+ T cells in HPV-induced lesions of K14-HPV16 transgenic mice

Abstract: Aims: Human papillomavirus (HPV) is a known biologic carcinogen which is commonly transmitted through sexual intercourse. CD8 + T cells are known effectors against tumour cells and an important prognostic marker in HPV-induced cancers. COX-2 inhibitors enhance CD8 + T cell activity against some cancers. In this work, we sought to study the presence and activation of CD8 + T lymphocytes in lesions from K14-HPV16 transgenic mice and the immunomodulatory effect of celecoxib (CXB) over these cells.Main methods: Sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…In fact, HPV oncoproteins are known to upregulate NF‐κB signaling during tumor progression as previously reviewed (Gil da Costa et al, ; Xu et al, ). Multiple anti‐inflammatory compounds have shown chemopreventive activity against HPV‐induced lesions in this model (Gil da Costa et al, ; Santos et al, ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, HPV oncoproteins are known to upregulate NF‐κB signaling during tumor progression as previously reviewed (Gil da Costa et al, ; Xu et al, ). Multiple anti‐inflammatory compounds have shown chemopreventive activity against HPV‐induced lesions in this model (Gil da Costa et al, ; Santos et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Our group and others recently characterized K14-HPV16 transgenic mice as a model to study HPV-driven carcinogenesis (Arbeit et al, 1994;Gil da Costa et al, 2017;Paiva et al, 2015a;Paiva et al, 2015b). Santos et al, 2016).…”
Section: Dmapt Partly Prevents Wasting Syndrome In Hpv16 +/− Micementioning
confidence: 99%
“…Our group has already studied the expression of two microRNAs miRNA-21 and miRNA-155 which are related to the inflammatory process in this model (14)(15). More recently, we showed that a relatively high dose (124 mg/kg/day) of celecoxib, a selective COX-2 inhibitor, promotes degranulation of CD8+ T cells in this model (17), while ptaquiloside, a natural immunosuppresive agent from Pteridium spp., down-regulates it (23).…”
Section: Discussionmentioning
confidence: 85%
“…K14-HPV16 transgenic mice target all HPV16 oncogenes to keratinized epithelia, reproducing essential molecular and morphological aspects of HPV16 induced premalignant lesions and various types of cancer (16). Using the same model, we also reported that the anti-inflammatory drug celecoxib, a selective cycloxigenase-2 (COX-2) inhibitor, is able to up-regulate degranulation of CD8 + T cells in HPV16 induced lesions (17). In the same experiment, celecoxib was also able to reduce the inflammation associated with HPV induced lesions and lesions' progression.…”
mentioning
confidence: 83%
“…Cyclooxygenase-2 (COX-2), a key mediator of inflammation, is involved in the development of multiple types of cancer, such as colon cancer, making it a useful therapeutic target [10,11,12,13]. We have previously shown that a specific COX-2 inhibitor, celecoxib, was able to block the progression of HPV16-induced lesions in transgenic mice [14]. However, oral administration of celecoxib induced significant mortality in HPV16 transgenic mice, indicating that it has unacceptable toxicity in our animal model.…”
Section: Introductionmentioning
confidence: 99%